NIRS-based prediction of mineral content and DCAD status for sustainable livestock nutrition - ROKHMATUN ISNAINI; DESPAL DESPAL; IDAT GALIH PERMANA; RIKA ZAHERA; ANNISA ROSMALIA; MUHAMMAD NAUFAL FARRAS (Society for Indonesian Biodiversity, 2025)
Abstract. Isnaini R, Despal, Permana IG, Zahera R, Rosmalia A, Farras MN. 2025. NIRS-based prediction of mineral content and DCAD status for sustainable livestock nutrition. Biodiversitas 26: 3281-3293. The Dietary Cation-Anion Difference (DCAD)—the balance between positively and negatively charged minerals (e.g., Na?, K? vs. Cl?, S²?)—is a key factor in maintaining acid-base balance, calcium homeostasis, and metabolic health in dairy cows (Bos taurus (Linnaeus, 1758)). However, DCAD data for individual feedstuffs, especially those used in tropical regions like Indonesia, are largely unavailable, limiting formulation accuracy. This study analyzed the mineral content (Ca, Na, K, Mg, P, S, Cl) of 289 Indonesian feed samples, all feed samples in each category were derived from one species only (66 grasses, 114 legumes, 47 roughages, and 62 concentrates) using wet chemistry, and calculated their DCAD values. Near-Infrared Reflectance Spectroscopy (NIRS) was used to develop predictive models as a rapid, non-destructive, cost-effective, and multi-parameter alternative to laboratory analysis. DCAD values varied widely: most grasses, roughages, and concentrates were negative, while legumes tended to be positive. This variation is nutritionally relevant, as negative DCAD diets are beneficial during the prepartum phase to reduce the risk of hypocalcemia in transition cows. NIRS models showed strong performance (R²>0.8; RPD>1.4), with successful external validation (SEP/SEL<2, except in concentrates). The resulting DCAD database and NIRS models can be integrated into mobile apps or formulation tools to support precision feeding strategies, particularly for managing transition cow health in tropical dairy systems.